Acoustic Performance of Green Composites for Chinese Traditional Percussion Drums - Gao, Qiang; Liu, Fanxizi; Wang, Keqin; Zhou, Mengjie; Lang, Chenhong; Guan, Fuwang; Cui, Lina; Zeng, Yongchun; Qiu, Yiping (Hua dong li gong da xue xue bao. Zi ran ke xue ban, 2020)
Flax and jute fabrics are adopted to reinforce epoxy matrix composites in order to explore the feasibility of replacing wood in percussion instruments. The fabrics are treated with alkaline solutions to improve interfacial adhesion between fibers and epoxy. The composites are fabricated using the hand-lay and vacuum assisted resin infusion process. Acoustic dynamic moduli, acoustic radiation damping coefficients, and acoustic impedances of the composites are tested and compared with those of the wood regularly used to make the percussion instruments. It is found that the acoustic properties of the composites are within the range of those of the wood, indicating that it could be feasible to replace the wood with natural cellulose fiber reinforced composites in percussion instrument production.